2003
DOI: 10.1248/cpb.51.138
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Non-Thiazolidinedione Antidiabetic Agents. 2. Novel Oxyiminoalkanoic Acid Derivatives as Potent Glucose and Lipid Lowering Agents.

Abstract: We previously reported that (Z)-2-{4-[(5-methyl-2-phenyl-1,3-oxazol-4-yl)methoxy]benzyloxyimino}-2-(4-phenoxyphenyl)acetic acid (3) showed potent glucose and lipid lowering effects in genetically obese and diabetic mice, KKA y . This compound also showed transcriptional activity for peroxisome proliferator-activated receptor (PPAR)-g g. We expanded on the structure-activity relationships of oxyiminoalkanoic acid derivatives based on this transcriptional activity (in vitro). Insertion of a carbon chain between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…plays the key role for in vivo glucose and lipid lowering activities, rather than its metabolites (2)(3)(4)(5). However, it is well known that the in vivo activities of compounds can be significantly different from their in vitro activities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…plays the key role for in vivo glucose and lipid lowering activities, rather than its metabolites (2)(3)(4)(5). However, it is well known that the in vivo activities of compounds can be significantly different from their in vitro activities.…”
Section: Resultsmentioning
confidence: 99%
“…2) TAK-559 also exhibits marked glucose and lipid lowering activities in insulin-resistant animal models, KKA y mice and Wistar fatty rats, 2,[10][11][12][13] and is under clinical trials. Metabolites M-I, M-II, M-III and M-IV were found during preclinical and clinical studies on TAK-559 (1), and their proposed structures are shown in Chart 1.…”
Section: -9)mentioning
confidence: 99%
See 3 more Smart Citations